Collaborative Strategic Reading (CSR) in Improving the English Department Students’ Reading Comprehension Achievement - Rojabi, Ahmad Ridho (JET ADI BUANA, 2018)
Reading as a receptive skill is very important skill for all students of English because it is a skill that everyone needs in studying or conveying the language. However, it is very difficult for the students to catch the message from the reading text as they have limited words and reading strategies. The aim of this research is to prove whether the implementation of Collaborative Strategic Reading (CSR) is effective to improve students’ reading comprehension.To achieve the purpose, the classroom action research design was employed by following four stages: planning, implementing, observing, and reflecting. This research was implemented in two cycles, in which both the first cycle and the second cycle were carried out in two meetings. CSR is implemented to teach students reading comprehension in cooperative learning groups. CSR consists of four strategies that are implemented in pre-reading, whilst reading, and post-reading. CSR strategies consist of: (1) preview the text, (2) click and clunk, (3) get the gist, and (4) wrap up. The result of the research revealed that Collaborative Strategic Reading (CSR) improved the students’ reading comprehension achievement on the fourth semester of English departmentat IAIN Jember. Keywords: collaborative strategic reading, reading comprehension achievement, classroom action research